Pengaruh Gaya Hidup, Kesadaran Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Dan Niat Membeli Kembali Sepatu Ventela Di Kota Bandung - Laksono, Indrawan Dimas; Sapuri, Marheni Eka (eProceedings of Management, 2024)
The footwear industry in Indonesia is experiencing development marked by continous variantions and evolving shoedesigns. Support from the head of the Indonesian Shoe Empowerment Center to small and medium-sized businesseswill continue to drive the development of local shoe products to meet market needs. This phenomenon is influencedby consumer awareness of local shoes, leading to rapid growth in the local footwear industry. In cities like Bandung,brands such as NAH Project, Brodo, Geoff Max, and Ventela have emerged. Ventela, as a pioneer among local brands,has improved the lifestyle of customers with its quality products, enhanced brand awareness, and demonstratedsupport for local shoe products. The purpose of this research is to examine the influence of lifestyle, brand awareness,and product quality on the purchasing decisions and repurchase intentions of Ventela shoes in Bandung. This researchuses quantitative methods with descriptive analysis research type. Sampling was carried out using a non probabilitysampling method with purposive sampling type, and there were 110 respondents. The data analysis technique usesPartial Least Square Structural Equation Modeling (SEM) with SmartPLS 3 software. Based on the research results,it shows that lifestyle has a significant influence on purchasing decisions. Brand awareness has a significant influenceon purchasing decisions. Product quality has a significant influence on purchasing decisions. Purchase decisionshave a significant effect on repurchase intentions.Keywords-lifestyle, brand awareness, product quality, purchase decision, repurchase intention